Effects of prostatic inflammation on LUTS and alpha blocker treatment outcomes - Ha Na Lee; Tae-Hyoung Kim; Sun-Ju Lee; Won Yeol Cho; Bong Suk Shim (International Brazilian Journal of Urology, 2014)
Purpose To evaluate the association between prostatic inflammation and lower urinary tract symptoms (LUTS), and to identify the effects of prostatic inflammation on the treatment with an alpha blocker. Materials and Methods 111 Participants who were aged ≥ 50 years, the presence of LUTS (maximal flow rate < 20 m/s, IPSS ≥ 11), and an elevated PSA level (3-20ng/mL) were treated with tamsulosin 0.2mg once daily for 3 months after prostate biopsies. Prostatic inflammation was scored as none (0), mild (I), moderate (II), or marked (III). LUTS parameters including urine flow rates, IPSS, PSA, and prostate volume were evaluated. Results Inflammation grading resulted in 25, 60, and 26 patients that were grade 0, I, and II, respectively. Lower grade inflammation was related to higher urine flow rate at baseline. Patients with higher inflammation grades had larger prostate volumes, larger total and transitional zone volumes, and higher PSA levels. Overall, urine flow rates and residual urine volume were improved after 3 months of alpha blocker therapy. Eighty percent of patients with grade 0 inflammation, 73% of patients with grade I inflammation, and 92.3% of patients with grade II inflammation showed improvement of LUTS after treatment. Longer duration of treatment was related to a decreased chance of improvement of LUTS. Patients with increased IPSS voiding subscales could be predictive of improvement of LUTS. Conclusions Patients with high grade inflammation had lower flow rates and higher prostatic volumes than patients with low grade inflammation. Inflammation grade did not affect the outcomes of alpha blocker treatment.